La provincia dell'Arpione Occidentale nei testi egiziani : ricerche storiche, geografiche e religiose dalle origini all'Epoca Romana - Tiribilli, Elena (Archaeopress Egyptology, 2023)
This monograph is devoted to a comprehensive study of the Western Harpoon province - the seventh nome of Lower Egypt - located in the north-western Delta. The book and aims to reconstruct its history and religious geography through textual sources, from its origins to the end of the Roman era.